2019
DOI: 10.4103/sajc.sajc_336_18
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis on efficacy of auto fluorescence in detecting the early dysplastic changes of oral cavity

Abstract: Background:Light-based detection agents using autofluorescence may be helpful in the detection of early dysplasia, which would otherwise be misdiagnosed as nondysplastic by conventional oral examination (COE) with white light. Visually-enhanced lesion scope (VELscope) is one of such an aid used for the purpose. A meta-analysis was carried out on the sensitivity and specificity of VELscope that would enable in providing evidence of its usage in oral dysplasia.Materials and Methods:MeSH terms such as auto flores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Although no details of the statistical analyses used in their study were reported, the methods were not likely adequate since only individual sensitivity and specificity values were described without their summation, AUC, or DOR. Thus, the study by Chaitanya et al 41 represents a narrative or systemic review based on individual study results rather than a meta‐analysis. The overall effect of autofluorescence on the diagnostic accuracy could not be evaluated using descriptive methods because the values were not weighted according to the number of enrolled patients 42,43 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although no details of the statistical analyses used in their study were reported, the methods were not likely adequate since only individual sensitivity and specificity values were described without their summation, AUC, or DOR. Thus, the study by Chaitanya et al 41 represents a narrative or systemic review based on individual study results rather than a meta‐analysis. The overall effect of autofluorescence on the diagnostic accuracy could not be evaluated using descriptive methods because the values were not weighted according to the number of enrolled patients 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis by Chaitanya et al 41 examined the ability of autofluorescence to detect cancer and precancerous lesions in 2019. The sample size of the included studies ranged from 43 to 200 patients (mean, 106 patients per study).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations